2021
DOI: 10.3389/fanim.2021.769334
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Surviving on Adrenaline: Developmental Programming Responses to Chronic Fetal Hypercatecholaminemia Contribute to Poor Muscle Growth Capacity and Metabolic Dysfunction in IUGR-Born Offspring

Abstract: Maternofetal stress induces fetal programming that restricts skeletal muscle growth capacity and metabolic function, resulting in intrauterine growth restriction (IUGR) of the fetus. This thrifty phenotype aids fetal survival but also yields reduced muscle mass and metabolic dysfunction after birth. Consequently, IUGR-born individuals are at greater lifelong risk for metabolic disorders that reduce quality of life. In livestock, IUGR-born animals exhibit poor growth efficiency and body composition, making thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 105 publications
(246 reference statements)
1
3
0
Order By: Relevance
“…Moreover, it should be noted that some studies found no changes in IUGR muscle content of Glut1 or Glut4 ( Limesand et al, 2007 ; Garg et al, 2009 ). Not surprisingly, Glut1 expression in the brain was increased by over 60% in IUGR fetal lambs and rats as well as in IUGR-born neonatal rats ( Sadiq et al, 1999 ; Limesand et al, 2007 ), which is consistent with brain sparing during chronic hypoglycemia ( Gibbs and Yates, 2021 ).…”
Section: Characteristics Of Iugrsupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, it should be noted that some studies found no changes in IUGR muscle content of Glut1 or Glut4 ( Limesand et al, 2007 ; Garg et al, 2009 ). Not surprisingly, Glut1 expression in the brain was increased by over 60% in IUGR fetal lambs and rats as well as in IUGR-born neonatal rats ( Sadiq et al, 1999 ; Limesand et al, 2007 ), which is consistent with brain sparing during chronic hypoglycemia ( Gibbs and Yates, 2021 ).…”
Section: Characteristics Of Iugrsupporting
confidence: 65%
“…Circulating norepinephrine (the primary fetal adrenal catecholamine) was elevated by as much as 8-fold in IUGR fetal sheep, and hypercatecholaminemia was among the earliest indicators of placental insufficiency ( Macko et al, 2013 ; Chang et al, 2019a ). Catecholamines are most associated with physiological mechanisms aimed at immediate survival, and sustained exposure of tissues can disrupt β adrenergic programming, the details and implications of which have been reviewed elsewhere ( Yates et al, 2011 ; Posont et al, 2017 ; Gibbs and Yates, 2021 ). Perhaps the most consequential effect of fetal hypercatecholaminemia is suppressed insulin activity.…”
Section: Characteristics Of Iugrmentioning
confidence: 99%
“…Heat stress during pregnancy induces intrauterine growth restriction (IUGR) of the placenta and fetus, which results in low birthweight of the offspring (Limesand et al, 2018;Beede et al, 2019). Stress-altered fetal programming of skeletal muscle disproportionally reduces that tissue's growth potential, which in turn diminishes growth efficiency, carcass yield, and value in livestock (Gibbs and Yates, 2021;Hicks and Yates, 2021) and contributes to metabolic health disorders in humans (Brown and Hay, 2016). Offspring born with low birthweight due to IUGR have hallmark deficiencies in lean muscle mass and greater propensity for fat deposition, which results in asymmetric body composition (Bell and Greenwood, 2016;Gibbs et al, 2019;Greenwood and Bell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle is a target tissue for stress-induced thrifty fetal programming, and its disproportional impairment relative to brain and skeletal growth leads to the hallmark asymmetric intrauterine growth restriction ( IUGR ) of the chronically stressed fetus [ 1 , 2 ]. Programmed changes in IUGR fetal muscle contribute to metabolic adaptations that manifest in late gestation [ 3 , 4 ] and predispose afflicted individuals to lifelong metabolic dysfunction [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In skeletal muscle and myoblasts (i.e., muscle stem cells), β2 adrenoceptors comprise about 90% of the adrenergic receptor populations [ 15 , 16 ], and their reduction is the primary mechanism of desensitization. Reduced skeletal muscle β2 adrenoreceptor content persists in IUGR-born offspring and coincides with diminished muscle mass and oxidative metabolism [ 2 , 14 , 17 ]. Abhorrent adrenergic regulation of IUGR pancreatic islets also disrupts insulin production and secretion, although this is primarily due to α adrenergic changes [ 13 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%